Tradicionalne vrednote, kvantitativna rast in kakovosten razvoj - Jukić, Tihomir (Urbani izziv, 2002)
Osijek Rehabilitation Rehabilitation srategy Urban development Urban master plan The key factors for a successful city rehabilitation project are continuity and implementation of projects significant for the development of the local community, together with owners of real estate and decision-makers that will support the proposed projects. Successful town renewal can be achieved in conditions when local needs and possibilities are recognised and efficient and flexible approaches appropriate for different situations and circumstances made available
Keywords: mesta; Osijek; prenova; prostorski razvoj; prostorsko urejanje; urbanism; urbanizem